Pengaruh Lingkungan Kerja Fisik Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada J&T Express Drop Center 10a Depok - Dzikry Apri Pandawangi; Amirudin Amirudin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study was to determine the effect of work discipline and work environment both partially and simultaneously on employee performance at J&T Express Drop Center 10A Depok with a sample of 77 employees. The method used is a quantitative method. Data analysis used in this study is the classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t test and F test. The results of this study are Physical Work Environment and Work Discipline have a significant effect on employee performance on the regression Y = 3.176 + 0.934 X1, the correlation value is 0.370 meaning that the two variables have a strong level of relationship. work environment has a significant effect on employee performance with the regression equation Y = 3.414 + 0.946 X2, the correlation value is 0.611 meaning that the two variables have a very strong level of relationship. Work environment and Work Discipline simultaneously have a significant effect on employee performance with the regression equation Y = 1.537 + 0.370 X1 + 0.611 X2. The coefficient of determination value is 89.5%, while the remaining 10.5% is caused by other variables not examined in this study. The results of testing the first hypothesis obtained a calculated t value> t table or (25.281> 1.992). Based on the results of testing the second hypothesis, the calculated t value> t table or (6.821> 1.998). Based on the results of testing the third hypothesis, the calculated F value> F table or (837.665> 3.120) was obtained. This shows that simultaneously the variables of work environment and work discipline have a significant influence on employee performance.